Advances in the biology and therapy of chronic myeloid leukemia: proceedings from the 6th Post-ASH International Chronic Myeloid Leukemia and Myeloproliferative Neoplasms Workshop. Issue 6 (June 2013) - van Etten, Richard A.; Mauro, Michael; Radich, Jerald P.; Goldman, John M.; Saglio, Giuseppe; Jamieson, Catriona; Soverini, Simona; Gambacorti-Passerini, Carlo; Hehlmann, Rüdiger; Martinelli, Giovanni; Perrotti, Danilo; Scadden, David T.; et al.
Abstract: Following the 53rd annual meeting of the American Society of Hematology (ASH) in San Diego in December 2011, a group of clinical and laboratory investigators convened for the 6th Post-ASH International Workshop on Chronic Myeloid Leukemia (CML) and Myeloproliferative Neoplasms (MPN). The Workshop took place on 13–14 December at the Estancia, La Jolla, California, USA. This report summarizes the most recent advances in the biology and therapy of CML that were presented at the ASH meeting and discussed at the Workshop. Preclinical studies focused on the CML stem cell and its niche, and on early results of deep sequencing of CML genomes. Clinical advances include updates on second- and third-generation tyrosine kinase inhibitors (TKIs), molecular monitoring, TKI discontinuation studies and new therapeutic agents. A report summarizing the pertinent advances in MPN has been published separately.